Public Perception of Facial Fillers - Hojjat, Houmehr; Raad, Richard; Lucas, Jordyn; Mir, Mohammad; Smith, Brendan C.; Carron, Michael A.; Zuliani, Giancarlo (Facial Plastic Surgery, 2019)
There has been widespread coverage of cosmetic procedures, particularly facial fillers, as minimally invasive options for facial rejuvenation. The authors' objective was to characterize news media's coverage of facial fillers and its role in shaping public perception of these products over the past decade. Public view plays a significant role in policymaking, assisting patient communication, and addressing preconceived notions. Google News was searched for online news coverage related to “facial fillers” from 2008 to 2017. News articles from various sources were reviewed and analyzed with multiple objectives including complications listed, advantages, disadvantages, physician specialties, overall theme of the articles as positive, negative, or neutral and other parametrics. A chi-square test was used for statistical analysis. Of 426 articles meeting inclusion criteria, international news (20.4%), tabloids (18.8%), online health sites (18.3%), and national news (16.9%) were represented. Of articles containing adequate information, coverage was 44.7% positive, 29.9% neutral, and 26.1% negative with no significant change from 2008 to 2017. In addition, 46.0% of papers discussed complications including vascular injury and blindness associated with fillers, with significant increase by 2017 (p < 0.05). Facial fillers media coverage was overall positive, with broad coverage at both national and international levels. Complications were discussed often, and although vascular injury and vision damage are rare complications of fillers, they were frequently cited, potentially leading the public to believe they occur frequently. There were also significant concerns in the news media about greater regulation of products used as facial fillers, and practitioners administrating them. Altogether, these findings provide a comprehensive overview of patient perception and expectations of an increasingly popular and expanding cosmetic procedure.
Keywords: facial fillers; demographics; public perception; Google News